Deaf Individuals Show a Leftward Bias in Numerical Bisection. (January 2016) - Cattaneo, Zaira; Cecchetto, Carlo; Papagno, Costanza
Consistent evidence suggests that deaf individuals conceive of numerical magnitude as a left-to-right-oriented mental number line, as typically observed in hearing individuals. When accessing this spatial representation of numbers, normally hearing individuals typically show an attentional bias to the left (pseudoneglect), resembling the attentional bias they show in physical space. Deaf individuals do not show pseudoneglect in representing external space, as assessed by a visual line bisection task. However, whether deaf individuals show attentional biases in representing numerical space has never been investigated before. Here we instructed groups of deaf and hearing individuals to quickly estimate (without calculating) the midpoint of a series of numerical intervals presented in ascending and descending order. Both hearing and deaf individuals were significantly biased toward lower numbers (i.e., the leftward side of the mental number line) in their estimations. Nonetheless, the underestimation bias was smaller in deaf individuals than in the hearing when bisecting pairs of numbers given in descending order. This result may depend on the use of different strategies by deaf and hearing participants or a less pronounced lateralization of deaf individuals in the control of spatial attention.